2012
DOI: 10.1186/1741-7015-10-108
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and prostate cancer: gene expression signature of human periprostatic adipose tissue

Abstract: BackgroundPeriprostatic (PP) adipose tissue surrounds the prostate, an organ with a high predisposition to become malignant. Frequently, growing prostatic tumor cells extend beyond the prostatic organ towards this fat depot. This study aimed to determine the genome-wide expression of genes in PP adipose tissue in obesity/overweight (OB/OW) and prostate cancer patients.MethodsDifferentially expressed genes in human PP adipose tissue were identified using microarrays. Analyses were conducted according to the don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 59 publications
2
79
0
1
Order By: Relevance
“…Adipose tissue surrounding invasive breast cancers exhibits increased expression of antiinflammatory genes, such as those encoding macrophage receptor with collagenous structure (MARCO) and V-Set and immunoglobulin domain containing 4 (VSIG4), while genes differentially expressed between tumour-adjacent and distant adipose tissue including those encoding secreted phosphoprotein 1 (SPP1), ribonucleotide reductase M2 (RRM2), and matrix metalloproteinase 9 (MMP9), are associated with increased cellular proliferation, invasion, and angiogenesis [68]. Moreover, in prostate cancer, gene expression signatures are different in tumours from obese versus lean cohorts [69]. Cultured media from prostate cancer cells stimulated adipokine production (osteopontin, TNF-/, and IL-6) from periprostatic adipose tissue, which in turn promoted tumour proliferation and invasiveness [70].…”
Section: The Tumour Microenvironment: Role Of Peritumoural Fat and Immentioning
confidence: 98%
“…Adipose tissue surrounding invasive breast cancers exhibits increased expression of antiinflammatory genes, such as those encoding macrophage receptor with collagenous structure (MARCO) and V-Set and immunoglobulin domain containing 4 (VSIG4), while genes differentially expressed between tumour-adjacent and distant adipose tissue including those encoding secreted phosphoprotein 1 (SPP1), ribonucleotide reductase M2 (RRM2), and matrix metalloproteinase 9 (MMP9), are associated with increased cellular proliferation, invasion, and angiogenesis [68]. Moreover, in prostate cancer, gene expression signatures are different in tumours from obese versus lean cohorts [69]. Cultured media from prostate cancer cells stimulated adipokine production (osteopontin, TNF-/, and IL-6) from periprostatic adipose tissue, which in turn promoted tumour proliferation and invasiveness [70].…”
Section: The Tumour Microenvironment: Role Of Peritumoural Fat and Immentioning
confidence: 98%
“…Excess adiposity modifies the expression profile of adipose tissue genes to ultimately foster growth of fat mass via an upregu lation of genes related to cellular activity (increased cell proliferation or differentiation, cell cycle activation and inhibition of apoptosis) and mild immuno inflammatory processes (reduced immunosurveillance). 53 Adipocytes and infiltrating immune cells secrete pro inflammatory adipo kines and cytokines, growth factors, metalloproteinases, and reactive oxygen species, which can induce DNA damage and chromosomal instability, thereby favouring carcinogenesis. 114 Conversely, growing tumour cells frequently extend beyond the primary organ in which they developed towards surrounding fat depots, thereby contributing to tumour progression and meta stasis.…”
Section: Weight-loss-dependent Effectsmentioning
confidence: 99%
“…21,43 Interestingly, the incidence of cancer and cancer-related death occurs in a setting that provides a unique adipose tissue microenvironment with concomitant systemic endocrine alterations that favour both tumour initiation and progression. 53,65 Low-grade chronic inflammation, dysregulation of growth signalling pathways, hyperinsulinaemia and hypoxia associated with increased adiposity are widely accepted as important factors that link obesity and cancer patho genesis. 64,65 White adipose tissue constitutes a relevant source of growth factors, adipokines and stromal progenitor cells.…”
Section: Weight-loss-dependent Effectsmentioning
confidence: 99%
“…Fat tissue produces hormones called adipokines, which can stimulate or inhibit cell growth [51]. It has been shown that, in obese patients, periprostatic adipose tissue displays hypercellularity and reduced immune surveillance, promoting a favourable environment for the development of prostate cancer [52].…”
Section: Obesity and Urological Cancermentioning
confidence: 99%